THE LEGAL FORCE OF IMPLEMENTING SEMA NUMBER 2 OF 2023 REGARDING INTERFAITH MARRIAGES BASED ON THE PERSPECTIVE OF LEGAL CERTAINTY - Pulungan, Muhammad Al Faisal; Pujiyono, Pujiyono; Saptanti, Noor (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
In general, everyone wishes to marry someone of the same faith so they can build and nurture a family with the same religion. However, in reality, interfaith marriages often occur in society due to unlimited human interactions and socialization, especially because Indonesia is a diverse country with many religious followers. The fact is, all religions in Indonesia prohibit interfaith marriages. In Law Number 1 of 1974 concerning marriage, Article 2 paragraph (1) states that